2015
DOI: 10.1103/physrevc.91.034605
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of projectile fragmentation in theSn112+Sn112and<

Abstract: We analyze the production cross sections and isotopic distributions of projectilelike residues in the reactions 112 Sn + 112 Sn and 124 Sn + 124 Sn at an incident beam energy of 1 GeV/nucleon measured with the fragment separator at the GSI laboratory. Calculations within the statistical multifragmentation model for an ensemble of excited sources were performed with ensemble parameters determined previously for similar reactions at 600 MeV/nucleon. The obtained good agreement with the experiment establishes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…6 (a) The fragments with atomic numbers Z > 10 in the 1A GeV 112,124 Sn + 112,124 Sn reactions have also been measured at FRS at GSI by Föhr et al [61]. The cross sections of the fragments in these reactions have been studied in theories, such as the statistical multifragmentation model (SMM) [62], and the EPAX3 parametrizations [63]. The temperatures of the fragments have been analyzed by using the isobaric ratio methods [34].…”
Section: A ∆B and ∆Lnr Distributionsmentioning
confidence: 99%
“…6 (a) The fragments with atomic numbers Z > 10 in the 1A GeV 112,124 Sn + 112,124 Sn reactions have also been measured at FRS at GSI by Föhr et al [61]. The cross sections of the fragments in these reactions have been studied in theories, such as the statistical multifragmentation model (SMM) [62], and the EPAX3 parametrizations [63]. The temperatures of the fragments have been analyzed by using the isobaric ratio methods [34].…”
Section: A ∆B and ∆Lnr Distributionsmentioning
confidence: 99%
“…Therefore, one may need additional approximations assumed to be combined with the SMM, such as stochastic nucleon transfer models, which may offer a good description of the transfer reactions near the Coulomb barrier. On the other hand, in our recent analyses we investigated the effect of the neutron richness of target nuclei on the projectile fragments and found that there was not a considerable influence of targets in projectile fragmentation reactions at relativistic [14,15,33], and Fermi energies [29][30][31]. However, in the present analysis we have noticed that the significant effect of the target on the neutron richness of the produced isotopes near Coulomb barriers should be taken into account.…”
Section: Discussionmentioning
confidence: 52%
“…At higher energies, the fragment characteristics are described according to the statistical and other existing models [18][19][20][21]. The predicted results obtained in these models have been seen to be consistent with the experimental data [14][15][16][17][18][19][20]. In the simulation of the reaction processes, one generally describes an intermediate excited nucleus formation in the first stage, and in the second stage, a secondary excitation process (deexcitation) of excited sources is simulated with an evaporation code.…”
Section: Statistical Modelmentioning
confidence: 56%
“…In this work we consider the generalization of the evaporation developed in Refs. [18,30,[33][34][35], and extend it for hyper matter. For excited hyper-nuclei the modification of the standard evaporation scheme is the following: Besides emission of normal light particles (nucleons, d, t, α, and others up to oxygen) in ground and particlestable excited states [30], we take into account the emission of strange particles (Λ-hyperon, 3 Λ H, 4 Λ H, 4 Λ He, 5 Λ He, and 6 Λ He).…”
Section: B Sequential Decay Models: Evaporation and Fissionmentioning
confidence: 94%